Preliminary Phytochemical Screening, Quantification of phenolic compounds, of Plant Extract from Chenopodium quinoa - kadri, mounira (Algerian Journal of Biosciences, 2021)
The aim of this study was to screening the phytogenic chemical compounds of the seeds of Chenopodium quinoa, obtained from Wilaya of El-oued. The chemical study showed that the plant contained a number of secondary metabolites, flavonoids, tannins, saponins, steroids and triterpenes, glycosids while the absence of alkaloids and comarin in Chenopodium quinoa. Folin-Ciocalteau colorimetric were used to determine the total phenolic con-tent (TPC), in the hydroalcoholic seeds extracts. The yield of the methanolic extract was estimated at 36.66%. As for the quantitative content of polyphenols, it is 11.647 ± 1.91µg AGE / mg extrait From this, Chenopodium quinoa is considered a nutritional and therapeutic value because it contains secondary metabolites